Elevated THOC5 expression in liver cancer and its implications for tumor progression and therapeutic response - Pang, Jin-Shu; Yang, Yu; Liang, Li; Zhao, Yu-Jia; Li, Jin-Dan; Li, Li-Peng; Wei, Xue-Xin; Gao, Rui-Zhi; Wen, Rong; He, Yun; Yang, Hong; Bai, Xiu-Mei (Frontiers in Medicine, 2025)
PurposeCancer remains a major global cause of death, with rising incidence influenced by environmental factors. The THOC5 gene, part of the THO complex, has emerged as a potential regulator in cancer biology. This study investigates THOC5 expression across various cancers, its role in prognosis, and its potential therapeutic implications, particularly in liver hepatocellular carcinoma (LIHC).MethodsWe analyzed THOC5 expression and its prognostic significance across various cancer types using globally available public datasets. Single-cell RNA sequencing, in-house RNA-seq, immunohistochemistry, and proteomic analysis were employed to further validate THOC5 expression and prognosis in LIHC. Functional assays, including wound-healing and Transwell migration, were performed following THOC5 knockdown in LIHC cell lines. A drug sensitivity analysis was performed to identify therapeutic agents associated with THOC5 expression levels.ResultsResults indicate that THOC5 is overexpressed in various cancers and correlates with unfavorable prognosis. In LIHC, both THOC5 mRNA and protein was confirmed to be overexpressed in LIHC elevated THOC5 correlated with advanced tumor stages and poor survival outcomes. THOC5 knockdown suppressed in vitro cell proliferation, migration, and invasion. Additionally, high THOC5 expression was linked to increased immune cell infiltration and enhanced sensitivity to certain chemotherapy agents, though it predicted poor response to immune checkpoint blockade therapy. Furthermore, high THOC5 was also indicated to activate several tumor signaling pathways, such as EGFR, Hypoxia and MAPK pathways.ConclusionTHOC5 could be a prognostic biomarker and therapeutic target in LIHC and various cancers, providing alternative treatment options when immunotherapy fails.